Tourism Bus Rental Application Design in PO. Padi Mas Using the Prototype Method - Dafit Setiawan Jaya; Uce Indahyanti (Procedia of Engineering and Life Science, 2022)
PO. Padi Mas is a company engaged in a tourism bus rental. Due to the large number of tourism bus procurements that need to be handled, a tool is needed, but in PO. Padi Mas, which is engaged in the transportation of bus rental systems, still uses manual processes in the payment system, data collection, and bus orders made by consumers, so it takes time for employees in this regard. Based on the existing problems, the author intends to create a web-based tourism bus rental application, aiming that the system used can further facilitate employee performance. The method used in software development is using the prototype method. The results of this study are web-based applications that are able to provide solutions to problems that exist in PO. Padi Mas assists customers in ordering buses and assisting PO. Padi Mas in administrative records has become more efficient.